Participatory Roles and Regulation Strategies in Groups Encountering Challenges - Channa, Faisal; Näykki, Piia; Häkkinen, Päivi (Small group research, 2025)
This study investigated participatory roles in high-performing (HPG) and low-performing (LPG) groups in collaborative learning, and how groups encountered challenges and regulated their learning. Participants, pre- and in-service teachers, ( n = 30) in groups of three were videotaped for analysing socially shared regulation of learning (SSRL). Social network analysis (SNA) was used for the analysis. The results showed that in both HPG groups and LPG groups, one group member remained peripheral. SNA revealed that HPG members engaged in more diverse interactions than LPG members. The study has theoretical and methodological implications for research on socially shared regulation of learning.